(untitled) (Journal of Nematode Morphology and Systematics, 2012)
A population identified as belonging to Acrobeloides uberrinus Anderson, 1965 is described from sand with some organic material in Senegal, and a population of Acrobeloides syrtisus Yeates, 1967 is described from the sand dunes of the type locality in New Zealand. Both species are studied under light microscopy (LM) and A. uberrinus is also studied under scanning electron microscopy (SEM), providing some new information on the variability of the species. The two populations are compared with their respective original descriptions, other populations of A. uberrinus, and with the closely related species A. setosus Brzeski, 1962 and A. tricornis (Thorne, 1925) Thorne, 1937. Acrobeloides setosus, A. uberrinus and A. syrtisus are considered to be synonyms of A. tricornis.